Marketing strategy of One village One Product new Media Matrix Marketing in Thailand - Zhang, Yixiao; Bi, Chuanchen (Technium Social Sciences Journal, 2022)
In order to protect and inherit Thai national culture and help farmers to overcome difficulties, the Thai government launched the "One Village, One Product" project, aiming at the deep processing products of local natural resources used by villages and towns to make traditional products with cultural connotations and related ecological industries. Through opening exhibition windows in the tourist areas, overseas trade fairs and e-commerce websites to provide online ordering service and other ways. However, in recent years, due to the epidemic and other adverse factors, the progress of marketing and implementation is in trouble. This article is based on the situation that the offline consumption power of traditional media is not optimistic due to the lack of publicity, and it propagates that the featured products of one village and one product in Thailand should be more in line with the trend of "Internet +". The new media matrix platform taking TikTok as an example has created a lower cost and higher quality industrial promotion channel for enterprises. By introducing the marketing matrix technology of new media, to promote the products through diversified media channels, to cover the vision of Chinese people as much as possible, to promote the excellent Thai "one village one product" products to the Chinese market, to bring new vitality to one village one product.